Cardiac arrest in an obstetric patient using remifentanil patient‐controlled analgesia. (7th January 2013) - Marr, R.; Hyams, J.; Bythell, V.
Summary: This case report describes the management of a patient, diagnosed with an intrauterine death at 31 weeks' gestation, who suffered a cardiorespiratory arrest during her induced labour while using a remifentanil PCA. She made a full recovery from resuscitation which included a peri‐mortem caesarean section.